2007
DOI: 10.1029/2007jd008538
|View full text |Cite
|
Sign up to set email alerts
|

Sequential variation of atmospheric mercury in Tokai‐mura, seaside area of eastern central Japan

Abstract: in 140.36°E), a small city on the Pacific side of central Japan. The concentration of atmospheric mercury in summer and autumn is higher than in winter and spring, and an 11-month average of 1-hour measurements is 3.78 ± 1.62 ng/m 3 (n = 7551). Our results showed that changes in the GEM level in Tokai-mura are largely determined by temperature and relative humidity, but are independent of wind speed and direction. Two contrary patterns were observed in the daily cycle of GEM concentrations: the most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These authors attributed the local atmospheric Hg(0) source to the emissions from industrial sectors in the region, with temporal patterns affected by anthropogenic and surface emissions, as well as atmospheric mixing and chemistry. Similar patterns were observed by Osawa et al [58], who measured atmospheric Hg(0) concentrations continuously during eleven months in Tokai-mura, Japan, and obtained an average concentration of 3.78 ± 1.62 ng m −3 (n = 7551). They suggested that changes in air Hg(0) concentrations were largely determined by temperature and relative humidity.…”
Section: Industrial Area-cnsupporting
confidence: 87%
See 2 more Smart Citations
“…These authors attributed the local atmospheric Hg(0) source to the emissions from industrial sectors in the region, with temporal patterns affected by anthropogenic and surface emissions, as well as atmospheric mixing and chemistry. Similar patterns were observed by Osawa et al [58], who measured atmospheric Hg(0) concentrations continuously during eleven months in Tokai-mura, Japan, and obtained an average concentration of 3.78 ± 1.62 ng m −3 (n = 7551). They suggested that changes in air Hg(0) concentrations were largely determined by temperature and relative humidity.…”
Section: Industrial Area-cnsupporting
confidence: 87%
“…The distribution was characterized by significant variations throughout the sampling campaign; however, these air Hg(0) concentrations were in the same range of those found in industrial sites worldwide (0.5-20 ng m −3 ) [57]. Similar air Hg(0) concentrations were found in Tokai-mura, a small city on the Pacific side of central Japan (3.78 ± 1.62 ng m −3 , [58]), and in a coastal site of the Penghu Islands, where Jen et al [59] reported seasonal and daily variations of the air Hg(0) concentrations with average values of 3.17 ± 1.06 ng m −3 but in a narrower range than ours (1.17-8.63 ng m −3 ). Air Hg(0) concentrations in CN were higher than those reported by Weiss-Penzias et al [60] in areas with anthropogenic Hg inputs in Nevada, USA (1.8 ± 1.4 ng m −3 ), although within the same range (0.6-18.1 ng m −3 ).…”
Section: Air Hg(0) Concentrations In Saltmarsh Vegetated Areasmentioning
confidence: 54%
See 1 more Smart Citation
“…To obtain this type of information, continuous monitoring with a high time resolution is required. However, such continuous Hg monitoring data is currently not available in Japan (Osawa et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Atmospheric Hg released from natural (e.g., volcanoes, volatilization from aquatic and terrestrial environments) (Pirrone et al, 2010;Strode et al, 2007) and anthropogenic sources (e.g., coal combustion, cement production, ferrous and non-ferrous metals manufacturing facilities, waste incineration and industrial boilers) (Pacyna et al, 2003(Pacyna et al, , 2006(Pacyna et al, , 2010Pirrone et al, 2010;Zhang et al, 2015) when introduced into terrestrial and aquatic ecosystem through wet and dry deposition (Mason and Sheu, 2002) can undergo various physical and chemical transformations before being deposited. Its lifetime in the atmosphere depends on its reactivity and solubility so that, depending on its form, it can have impacts on local, regional and global scales (Lin and Pehkonen, 1999;Lindberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%